(untitled) (Revista Internacional de Folkcomunicação, 2021)
From a theological-folkcommunicational perspective, this text examines, from the analysis of media coverage, the use of marijuana in the celebrations of the Church of the Humble (Maceió, Alagoas) as practice that characterizes religiosity marginal, counter-hegemonic and controversial religiosity of Christianity. In addition to rescuing uses of psychoactive substances in ceremonies of different religions, theological reflection focuses on the dimensions of religiosity, spirituality, charisma and sacrament, while the folkcommunicational evaluates the Church of the Humble as a culturally marginalized group whose opinion leaders communicate opposing and challenging ideas to the hegemonic Christian religious structure.